The Epistemological Divergence between the Ḥanafī and Shāfiʿī Madhhabs: The Ḥadīth Evaluation and Legal Reasoning on the Discourse of Gendered Fiqh - Wahda, Maziya Rahma; Alfikri, Ahmad Faiz Shobir; Rahmatullah, M. Azam (Universitas Islam Negeri Alauddin Makassar, 2025)
Prayer (ṣalāh) is governed by provisions outlined in the Qur’an and directly exemplified by the Prophet Muhammad (peace be upon him), and therefore must be followed by all Muslims, both men and women. However, there are procedural (kaifiyyah) differences between genders in prayer. This study aims to examine several kaifiyyah differences in prayer between men and women based on the perspectives of the Ḥanafī and Shāfiʿī madhhabs of thought. Utilizing normative or library research through a comparative approach, the analysis focuses on the arguments and methods of legal derivation (istinbāṭ) employed by both madhhabs. The findings indicate that the gender-based differences identified include the positioning of the hands during takbīrat al-iḥrām, the placement of the hands while standing, the posture in rukūʿ (bowing) and sujūd (prostration), the rules governing vocal recitation, and the manner of alerting the imām when an error occurs. Regarding the positioning of the hands during takbīrat al-iḥrām, while standing, and in vocal recitation, the Ḥanafī and Shāfiʿī madhhabs offer differing views. However, they concur on the procedures of rukūʿ, sujūd, and the method of notifying the imām for both men and women. Both madhhabs base the procedural distinctions on preserving a woman’s ʿawrah (parts of the body that must be covered). The epistemological divergence between the Ḥanafī and Shāfiʿī madhhabs is deeply rooted in their respective methodologies of ḥadīth evaluation and legal reasoning. Academically, this study contributes to the discourse of gendered fiqh by demonstrating how jurisprudential reasoning addresses ritual distinctions between men and women and highlighting the interpretive dynamism within Islamic law.